Measurement systems : application and design - Doebelin, Ernest O. (Boston : McGraw-Hill, 2004)
Presents an overview of measurement, instrumentation and experimentation. This book covers sensors and computer tools in measurement and experimentation. It discusses measurement techniques related to micro and nano-technologies.
Part 1 General Concepts 1 Types of Applications of Measurement Instrumentation 2 Generalized Configurations and Functional Descriptions of Measuring Instruments 3 Generalized Performance Characteristics of Instruments Part 2 Measuring Devices 4 Motion and Dimensional Measurement 5 Force, Torque, and Shaft Power Measurement 6 Pressure and Sound Measurement 7 Flow Measurement 8 Temperature and Heat-Flux Measurement 9 Miscellaneous Measurements Part 3 Manipulation, Transmission, and Recording of Data 10 Manipulating, Computing, and Compensating Devices 11 Data Transmission and Instrument Connectivity 12 Voltage-Indicating and -Recording Devices 13 Data-Acquisition Systems for Personal Computers 14 Measurement Systems Applied to Micro- and Nanotechnology
Includes bibliographical references and index.
Keywords: Measuring instruments; Physical measurements